Pathogenesis of Brain Arteriovenous Malformations - KOMIYAMA, Masaki (Neurol Med Chir (Tokyo), 2016)
Brain arteriovenous malformations (bAVMs) represent a high risk of intracranial hemorrhages, which are substantial causes of morbidity and mortality of bAVMs, especially in children and young adults. Although a variety of factors leading to hemorrhages of bAVMs are investigated extensively, their pathogenesis is still not well elucidated. The author has reviewed the updated data of genetic aspects of bAVMs, especially focusing on clinical and experimental knowledge from hereditary hemorrhagic telangiectasia, which is the representative genetic disease presenting with bAVMs caused by loss-of-function in one of the two genes: endoglin and activin receptor-like kinase 1. This knowledge may allow us to infer the pathogensis of sporadic bAVMs and in the development of new medical therapies for them.